2013
DOI: 10.3390/nu6010090
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Iron Status and Cognitive Function in Young Women Consuming Beef or Non-Beef Lunches

Abstract: Iron status is associated with cognitive performance and intervention trials show that iron supplementation improves mental function in iron-deficient adults. However, no studies have tested the efficacy of naturally iron-rich food in this context. This investigation measured the hematologic and cognitive responses to moderate beef consumption in young women. Participants (n = 43; age 21.1 ± 0.4 years) were randomly assigned to a beef or non-beef protein lunch group [3-oz (85 g), 3 times weekly] for 16 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 58 publications
(67 reference statements)
1
48
1
Order By: Relevance
“…Of the 1107 abstracts identified (1043 from database search and 64 from reference list checking), 184 full-text articles were retrieved. Forty-nine studies [ 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] met the inclusion criteria and were included in this review ( Figure 1 . PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 1107 abstracts identified (1043 from database search and 64 from reference list checking), 184 full-text articles were retrieved. Forty-nine studies [ 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] met the inclusion criteria and were included in this review ( Figure 1 . PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram).…”
Section: Resultsmentioning
confidence: 99%
“…Of the total number of participants, only 9.6% were male. Two studies [ 70 , 71 ] included exclusively all-male populations, compared with 29 studies [ 14 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 42 , 45 , 46 , 48 , 50 , 51 , 52 , 53 , 54 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 73 , 74 , 75 ] that included exclusively females. The remaining 18 studies included mixed gender populations [ 28 , 35 , 38 , 39 , 40 , 41 , 43 , 44 , 47 , 49 , 55 , 57 , 59 , 63 , 65 , 66 , 69 , 72 ], to which females frequently contributed greater than 50% of the study population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent meta-analysis, iron supplementation in young children suffering from ID anemia does not influence their Brought to you by | Bibliotheque de l'Universite Laval Authenticated Download Date | 7/13/15 9:57 AM cognitive function within the first 30 days after therapy initiation . However, in a randomized trial, Blanton (2014) observed that women consuming a naturally iron-rich diet experienced improved cognitive function.…”
Section: Neurologic and Psychiatric Manifestations Of Idmentioning
confidence: 96%
“…Teen blood donors are sometimes even warned by blood collectors in predonation educational materials to be careful about timing their blood donation so that it does not interfere with major tests or athletic events. This concern may be especially warranted in young women, as there is evidence that low iron is related to deficits in cognitive functioning [40,41,46]. For example, Blanton et al [41] recently found in healthy college-aged women that low iron status, in the absence of iron-deficiency anaemia, was related to a significant slowing of planning speed in a test of central executive function.…”
Section: Young Donors and Iron Deficiencymentioning
confidence: 99%